Emergent Large Vessel Occlusion Screen Is an Ideal Prehospital Scale to Avoid Missing Endovascular Therapy in Acute Stroke. Issue 9 (September 2018) - Suzuki, Kentaro; Nakajima, Nobuhito; Kunimoto, Kenta; Hatake, Seira; Sakamoto, Yuki; Hokama, Hiroyuki; Nomura, Koichi; Hayashi, Toshiyuki; Aoki, Junya; Suda, Satoshi; Nishiyama, Yasuhiro; Kimura, Kazumi
Abstract : Background and Purpose—: The strong evidence of endovascular therapy in acute ischemic stroke patients with large vessel occlusion (LVO) is revealed. Such patients are required to direct transport to the hospital capable of endovascular therapy. There are several prehospital scales available for paramedics to predict LVO. However, they are time consuming, and several of them include factors caused by other types than LVO. Therefore, we need a fast, simple, and reliable prehospital scale for LVO. Methods—: We developed a new prehospital stroke scale, emergent large vessel occlusion (ELVO) screen, for paramedics to predict LVO. The study was prospectively performed by multistroke centers. When paramedics referred to stroke center to accept suspected stroke patients, we obtain the following information over the telephone. ELVO screen was designed focusing on cortical symptoms: 1 observation; presence of eye deviation and 2 questions; paramedics show glasses, what is this? and paramedics show 4 fingers, how many fingers are there? If the presence of eye deviation or ≥1 of the 2 items were incorrect, ELVO screen was identified as positive. We evaluated between results of ELVO screen and presence of LVO on magnetic resonance angiography at hospital arrival. Results—: A total of 413 patients (age, 74±13 years; men, 234 [57%]) were enrolled. Diagnosis was ischemic stroke, 271 (66%); brain hemorrhage 73 (18%); subarachnoid hemorrhage, 7 (2%); and not stroke, 62 (15%). One hundred fourteen patients had LVO (internal carotid artery, 33 [29%]; M1, 52 [46%]; M2, 21 [18%]; basilar artery, 5 [4%]; P1, 3 [3%]). Sensitively, specificity, positive predictive value, negative predictive value, and accuracy for ELVO screen to predict LVO were 85%, 72%, 54%, 93% and 76%, respectively. Among 233 patients with negative ELVO screen, only 17 (7%) had LVO, which indicated to be an ideal scale to avoid missing endovascular therapy. Conclusions—: The ELVO screen is a simple, fast, and reliable prehospital scale for paramedics to identify stroke patients with LVO for whom endovascular therapy is an effective treatment.